2009
DOI: 10.1084/jem.20082900
|View full text |Cite
|
Sign up to set email alerts
|

Control of T helper cell differentiation through cytokine receptor inclusion in the immunological synapse

Abstract: The antigen recognition interface formed by T helper precursors (Thps) and antigen-presenting cells (APCs), called the immunological synapse (IS), includes receptors and signaling molecules necessary for Thp activation and differentiation. We have recently shown that recruitment of the interferon-γ receptor (IFNGR) into the IS correlates with the capacity of Thps to differentiate into Th1 effector cells, an event regulated by signaling through the functionally opposing receptor to interleukin-4 (IL4R). Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 83 publications
7
33
2
1
Order By: Relevance
“…Differentiation into Th1 or Th2 cells depends on the cytokines secreted in their vicinity, which then regulates and modulates the disease outcome. Indeed, previous studies have confirmed that early blocking of IFN-γ or IL-4 production shifts Th cell polarization, altering the disease outcome (28,42), strengthened by the selective recruitment of either IL-4Rα or the IFN-γ receptor to the immunological synapse in the absence of Th1-and Th2-inducing signals, respectively (43). Thus, naïve T cell precursors may be able to take advantage of cytokine-producing B cells as differentiation signals (44), strengthening the possibility that B cells can control and enhance inflammation and Th cell differentiation, not just as bystander cells but as direct participants.…”
Section: Discussionmentioning
confidence: 92%
“…Differentiation into Th1 or Th2 cells depends on the cytokines secreted in their vicinity, which then regulates and modulates the disease outcome. Indeed, previous studies have confirmed that early blocking of IFN-γ or IL-4 production shifts Th cell polarization, altering the disease outcome (28,42), strengthened by the selective recruitment of either IL-4Rα or the IFN-γ receptor to the immunological synapse in the absence of Th1-and Th2-inducing signals, respectively (43). Thus, naïve T cell precursors may be able to take advantage of cytokine-producing B cells as differentiation signals (44), strengthening the possibility that B cells can control and enhance inflammation and Th cell differentiation, not just as bystander cells but as direct participants.…”
Section: Discussionmentioning
confidence: 92%
“…We first sought to characterize the plasma membrane distribution of TGF-bRs treated with TGF-b in the presence or absence of anti-CD3/ CD28 stimulation. TCR binding to agonists induces capping of the TCRs that accumulate at one pole of the cell together with other receptors such as IFN-gR (44,45). Using confocal microscopy, we found that following TCR and TGF-b stimulation, TCRs and TGFbRI accumulated at the same pole of the cell (Fig.…”
Section: Cd3-cd28 Treatment Increases Colocalization Of Tgf-brs With mentioning
confidence: 84%
“…This notion is supported by recent reports showing serine phosphorylation of STAT-1 by T cell Ag receptor signaling (53) and the recruitment of S727-phosphorylated STAT-1 to the immunological synapse of Th precursor cells. In these cells S727-phosphorylation is required for Th polarization, but STAT-1 tyrosine phosphorylation is not (54). Determining the extent to which this IFN-independent STAT-1 phosphorylation impinges on T cell-mediated adaptive immunity will require future research with IFN-unresponsive mice expressing Stat1S727A.…”
Section: Discussionmentioning
confidence: 99%